2010
DOI: 10.1080/13573322.2010.493312
|View full text |Cite
|
Sign up to set email alerts
|

Workplace learning of high performance sports coaches

Abstract: The Australian coaching workplace (to be referred to as the State Institute of Sport; SIS) under consideration in this study employs significant numbers of fulltime performance sport coaches and can be accurately characterized as a genuine workplace. Through a consideration of the interaction between what the workplace (SIS) affords the individual and the agency of the individual SIS coaches, it is possible to gain an understanding how high performance sport coaches learn in the workplace. Analysis of data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 27 publications
1
48
0
3
Order By: Relevance
“…Research in coach development has shown that along with other sources (such as learning on the job), coaches develop their knowledge through social networks (Culver and Trudel 2006;Rynne, Mallett, and Tinning 2010). The football coaches in this study were found to be similarly engaged in regular interactions with other coaches who were seen as valuable sources in developing their coaching knowledge.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Research in coach development has shown that along with other sources (such as learning on the job), coaches develop their knowledge through social networks (Culver and Trudel 2006;Rynne, Mallett, and Tinning 2010). The football coaches in this study were found to be similarly engaged in regular interactions with other coaches who were seen as valuable sources in developing their coaching knowledge.…”
Section: Resultsmentioning
confidence: 57%
“…Of prime interest to some coaching researchers and coach educators has been how coaches learn in this turbulent and chaotic environment (Mallett 2010). The recent literature has been useful in highlighting how coaches learn (Gilbert and Trudel 2001;Cushion et al 2003;Jones, Armour, and Potrac 2003;Trudel and Gilbert 2004;Gilbert and Trudel 2005;Nelson, Cushion, and Potrac 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones (2007) was the first to exploit this territory of expression in sport coaching, and subsequently Bush and Silk (2012) have represented their data through a reflexive conversation, and, Nelson and Groom (2012) and Roberts and Potrac (2014) have both utilised hypothetical conversations. This paper also speaks to the call from Rynne, Mallett and Tinning (2010) of the need for the coaching workplace to be examined, as to date it has been a site that has been largely overlooked. Fictional writing allows us-the researcher and reader-to enter the coaching workplace and articulate it in a manner that deepens our understanding of this context and, according to Jones (2007, p.161), "allow the teasing-out of previous assumptions that trigger new ways of reasoning and doing".…”
Section: A Hypothetical Coaching Conversationmentioning
confidence: 99%
“…The CPD model espoused by the aforementioned researchers aligns well with Mallett, Rynne and Tinning's (2010) model of non-formal education. Mallett, et al (2010) suggest that coaches learn best through coaching and consequently are more likely to construct meaning from personal experiences rather than through participating isolated formalised learning opportunities.Using a participatory action research methodology, a coaching education intervention embracing the organising principles of a CPD and the skill acquisition principles of non-linear pedagogy was designed and implemented to determine if the behaviours and coaching practices of coaches could be enhanced. Two volunteer coaches within a volleyball school of excellence academy who demonstrated a traditional reductionist approach to coaching participated in two reflective research cycles.…”
mentioning
confidence: 99%